Waste Disposal Practices, Health Awareness and Challenges in Rapidly Growing Populations: A Case Study of Ede, Southwestern Nigeria - Aroge, Sunday Kayode; Anifowose, Adeleye Y. B.; Adarabioyo, Mumini Idowu (Geographica Pannonica, 2025)
Waste disposal and management have emerged as pressing challenges in urban areas, particularly in developing countries where rapid population growth exacerbates the situation. This study examines waste management practices, health awareness, and the associated challenges in Ede, Osun State, Nigeria. A structured questionnaire was distributed to 310 respondents using a simple random sampling method. The analysis revealed that waste disposal practices predominantly involve open burning (34.2%) and disposal in rivers/streams (26.8%), both of which pose significant environmental and health risks. Despite a high percentage of organic waste (74.2%), sustainable practices such as recycling (7.1%) and composting (3.2%) are minimally utilized. Using ordinal logistic regression, important predictors of waste disposal methods were found. These included lack of money, inadequate facilities, and low awareness. Additionally, dissatisfaction with waste management services correlated with poor waste disposal practices. The findings underscore the urgent need for enhanced public education, infrastructure improvements, and the promotion of sustainable waste management practices to mitigate environmental and health impacts in the study area.